Effects of androgen deprivation therapy on telomere length. (22nd June 2017) - Cheung, Ada S.; Yeap, Bu B.; Hoermann, Rudolf; Hui, Jennie; Beilby, John P.; Grossmann, Mathis
Summary: Objective: Recent evidence suggests that androgens either directly or via aromatisation to oestradiol may regulate telomere length, hence providing a mechanism whereby reproductive steroids are linked to biological ageing in men. Using men with prostate cancer initiating androgen deprivation therapy (ADT), we tested the hypothesis that severe sex steroid deprivation would accelerate telomere shortening. Design: We conducted a secondary analysis of a 2‐year prospective controlled study among 65 men with nonmetastatic prostate cancer newly commencing adjuvant ADT (n=40) and age‐ and radiotherapy‐matched prostate cancer controls (n=25). Methods: We measured leucocyte telomere length (LTL) expressed as telomeric/single copy control gene (T/S) ratio at baseline, 6, 12 and 24 months. Generalized linear models determined the mean adjusted difference (MAD) (95% confidence interval) between groups during follow‐up. Results: Compared to controls over 24 months, men receiving ADT had no change in LTL, MAD for T/S ratio (0.105 [−0.004; 0.213], P =.235). Conclusions: Using men with prostate cancer receiving ADT as a model we found no evidence that prolonged and profound sex steroid deprivation is associated with accelerated telomere shortening. Larger studies will be required to confirm or refute these findings.